2023
DOI: 10.3389/fpls.2023.1096091
|View full text |Cite
|
Sign up to set email alerts
|

H+-pyrophosphatases enhance low nitrogen stress tolerance in transgenic Arabidopsis and wheat by interacting with a receptor-like protein kinase

Abstract: IntroductionNitrogen is a major abiotic stress that affects plant productivity. Previous studies have shown that plant H+-pyrophosphatases (H+-PPases) enhance plant resistance to low nitrogen stress. However, the molecular mechanism underlying H+-PPase-mediated regulation of plant responses to low nitrogen stress is still unknown. In this study, we aimed to investigate the regulatory mechanism of AtAVP1 in response to low nitrogen stress.Methods and ResultsAtAVP1 in Arabidopsis thaliana and EdVP1 in Elymus dah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The second SNP, ss715610072 , is near the candidate gene Glyma.11G206700 . This gene is a cysteine-rich receptor-like kinase (CRK), which is a family of receptor-like kinases (RLKS) that are important in plant immunity, response to abiotic stress, and regulating growth and development (Zhang et al, 2023). CRKs are highly evolutionarily conserved across vascular plants and have been found to modulate the tradeoff between growth and stress response in many species (Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second SNP, ss715610072 , is near the candidate gene Glyma.11G206700 . This gene is a cysteine-rich receptor-like kinase (CRK), which is a family of receptor-like kinases (RLKS) that are important in plant immunity, response to abiotic stress, and regulating growth and development (Zhang et al, 2023). CRKs are highly evolutionarily conserved across vascular plants and have been found to modulate the tradeoff between growth and stress response in many species (Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This gene is a cysteine-rich receptor-like kinase (CRK), which is a family of receptor-like kinases (RLKS) that are important in plant immunity, response to abiotic stress, and regulating growth and development (Zhang et al, 2023). CRKs are highly evolutionarily conserved across vascular plants and have been found to modulate the tradeoff between growth and stress response in many species (Zhang et al, 2023). The SNP on chromosome 13 associated with DRB in heat has two promising candidate genes nearby, Glyma.13G223000 and Glyma.13G223100 .…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we propose that the use of nanotechnology in the future may further enhance the direct measurements of PPi. For instance, Zhang et al ( 2023a ; 2023b ) developed a carbon quantum dot system in which highly versatile carbon quantum dots are coupled to nanotubes synthesized using metal–organic frameworks. The detection method worked via a “turn-off” mechanism, where Cu 2+ ions quench the fluorescence from the quantum dots, and the detection is based on the decomposition of the metal–organic framework containing the Cu 2+ ions, which are released by the coordination of the Cu 2+ ions with PPi, leading to fluorescence recovery.…”
Section: Ppases and Applicationsmentioning
confidence: 99%
“…Concomitantly, the authors also investigated whether m-PPase could interact with other proteins and found that it interacts with the A. thaliana receptor-like protein kinase (AtRLK) protein via a yeast two-hybrid system and colocalization experiments. The most striking finding is that the AtRLK mutant and AtAVP1 mutant exhibit the same phenotype under low-nitrogen conditions ( Zhang et al, 2023b ). Overall, there are still aspects to uncover for m-PPases in plants; perhaps their roles in subcellular localization and protein interactions in plants may lead to future experiments that will help engineer plants tolerant to the increasing stress conditions in the soil, either as a direct effect of temperature or the secondary effects due to the reduction of rainfall and availability of nitrogen.…”
Section: Ppases and Applicationsmentioning
confidence: 99%
“…The functional characterization of AVP1 in A. thaliana has been established by studies in mutants and overexpression lines. Some of its known roles are regulation of auxin-mediated organ development and involvement in various abiotic stress tolerance ( Li et al., 2005 ; Kim et al., 2014 ; Nepal et al., 2020 ; Zhang et al., 2023 ). It has also been shown that rather than proton pumping, PPi hydrolysis activity is the major contribution of AVP1 in organ development as demonstrated using fugu5 mutants ( Ferjani et al., 2011 ; Asaoka et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%